'Sore love': R. L. Stevenson and leprosy on Penrhyn Island. Issue 1 (1st May 2017) - Manfredi, Carla
In 1890 Robert Louis Stevenson embarked upon his third Pacific Island cruise aboard the SS Janet Nicoll. During the next four months, the travel writer made several stops in the Cook Islands, including the atoll of Penrhyn or Togarewa (now Tongareva), where he learned about Penrhyn's leprasorium. This article examines two of Stevenson's rarely examined pieces concerning Penrhyn and discusses Stevenson's engagement with leprosy in the Pacific, its aetiology and effects, with respect to Polynesian cultural habits and customary practice, and to the colonial discourse on contagion. In his article 'A Pearl Island: Penrhyn' (New York Sun), Stevenson hypothesized that a single Hawaiian leper had escaped from Kalaupapa and reached the shores of Penrhyn. Stevenson's lament about the insidious Hawaiian leper's effects on the local population was accompanied by his photographic illustration of Penrhyn children who, throughout the course of the article, came to embody the inevitable destruction of a Pacific population. Just as Stevenson's vivid account of his family's visit to Penrhyn is woven around the presence of the singing girls, the photograph depicting them serves as a launching point for my discussion of Stevenson's representation of leprosy in both 'A Pearl Island: Penrhyn' and in the related essay entitled 'Talofa, Togarewa!' ('Goodbye, Togarewa!'). The latter was conceived for publication in the London Missionary's Samoan-language magazine O Le Sulu Samoa (Samoan Torch). In both 'A Pearl Island: Penrhyn' and 'Talofa, Togarewa!', the singing girls function as narrative prompts for Stevenson's detailed account of the link between leprosy and the Hawaiian Islands, but they – over the course of both texts – also become symbols for all that is destroyed (youth, innocence, joy, morality and bodily and spiritual health) through lethal contagion.